O estatuto e as instâncias da noção de semelhança no Livro I do Tratado da natureza humana de David Hume - Vinícius Amaral de Sousa (2020)
This Master’s thesis aims to investigate the existence of a statute that regulates the use of the concept of resemblance in Book I of Hume’s Treatise of Human Nature. To do so, at first, we analyze some central concepts of the book in question, such as perception, imagination, principles of association, philosophical and natural relations, in order to discuss and provide the basis for understanding how the resemblance between perceptions operates in the Imagination. As a second step, we gather eleven instantiations of “resemblance” in the Treatise, all of which possessed of fundamental argumentative or descriptive function for the development of Hume’s philosophy. We emphasize four senses of resemblance, namely resemblance as sharing qualities, resemblance as instance of a kind, resemblance as degrees, and as general appearance. In our hypothesis, comparison of these senses with the whole of the Treatise of Human Nature indicates that a reduction to only one kind of resemblance is not possible, the notion of resemblance is polymorphic, but we can find a structure that underlies its four kinds, according to a triadic model.